UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA KELAS VIII DI SMP PGRI 1 PALOH - Azlan Azlan (Tarbiya Islamica, 2017)
The purpose of this study is to reveal about: 1) Islamic Religious Education Teacher Program in improving the religious character of class VIII students at SMP PGRI 1 Paloh. 2) Strategies of Islamic Religious Education Teachers in improving the religious character of class VIII students at SMP PGRI 1 Paloh. 3) The aim is to improve the religious character of class VIII students at SMP PGRI 1 Paloh. And 4) Supporting and inhibiting factors in improving the religious character of class VIII students at SMP PGRI 1 Paloh in the 2020-2021 school year. This research uses a qualitative approach with the type of case study research. Data collection techniques Focus Group Discussion FGD in the form of observation, interviews and documentation. The data analysis techniques for the preliminary study are in the form of data reduction, data display, verification and conclusion drawing. The results showed that: 1) The program to improve the religious character of class VIII students at SMP PGRI 1 Paloh for the academic year 2020-2021 was carried out by Islamic Religious Education teachers, namely in two ways, inside and outside the classroom. The programs carried out are integrating character education content that has been formulated, integrating character education in daily activities at school, integrating character education into programmed activities, and building collaboration between parents and schools, in other words promoting habituation. 2) Strategies to improve the religious character of grade VIII students at SMP PGRI 1 Paloh for the 2020-2021 academic year carried out by Islamic Religious Education teachers are giving praise or gifts, define and drill, traits of the mouth I and counseling guidance. 3) The purpose of improving the religious character of students carried out by Islamic education teachers for class VIII at SMP PGRI 1 Paloh for the 2020-2021 school year is to direct students to become ulul albab humans, be able to determine one's character, and trigger students' personal awareness. 4) Supporting and inhibiting factors in improving the religious character of class VIII students at SMP PGRI 1 Paloh in the 2020-2021 school year that Islamic education teachers encountered, namely the habits and environment of the students themselves.